Three-Dimensional Graphene-Based Composite Hydrogel Materials for Flexible Supercapacitor Electrodes - Lai, Enping; Yue, Xinxia; Ning, Wan'e; Huang, Jiwei; Ling, Xinlong; Lin, Haitao (Frontiers in Chemistry, 2019)
Three-dimensional (3D) graphene-based hydrogels have attracted great interest for applicating in supercapcacitors electrodes, owing to their intriguing properties that combine the structural interconnectivities and the outstanding properties of graphene. However, the pristine graphene hydrogel could not satisfy the high-performance demands, especial in high specific capacitance. Consequently, the incorporation of graphene with a range of other materials to create novel composite hydrogels with increased electrochemical properties has been developed. In this mini review, a brief summary of recent progress in the research of the three-dimensional graphene-based composite hydrogel for flexible supercapacitors electrodes materials is presented. The latest progress in the graphene-based composite hydrogel consisting of graphene/metal, graphene/polymer, and doped graphene is discussed. Furthermore, future perspectives and challenges in graphene-based composite hydrogel for supercapacitor electrodes are also expressed.